Validation of Smartphone Sway Analysis for Fall Prevention - Matthew Cimera (MDPI AG, 2021)
Analysis of the balance and sway of the elderly remains a field continuously studied for additional means of assessing the risks of falls. Almost 50% of falls among the elderly lead to serious injuries, and falls are the leading cause of death for the elderly. Thus, the development of a convenient method to assess the risks of falling would be beneficial in helping to diminish these risks. We recorded the sway data by using the widely acceptable force plate and simultaneously compared it to the angular orientation measured by a cell phone’s accelerometer attached to the subject. It was found that the correlation of the average path length and average velocity between the results from the force plate and the phone application were 0.83 and 0.86 respectively. Overall, the direction of the strongest correlation was in the anterior–posterior (AP) direction that is mostly associated with falls. The smart phone application was able to represent the results that were gathered by the force plate, thus opening the door to a simpler way to track sway variables in the elderly without the necessity to come to a doctor’s office.